Bankers and Subsidies - Hansen, Alvin H. (The Review of Economics and Statistics, 1958)
T HE recent report of the Economic Policy Commission of the American Bankers Association entitled A Plan for Member Bank Reserve Requirements is a remarkable document. The bankers are, in effect, asking Congress to hand them on a silver platter $9.8 billions of earning assets in place of an equivalent amount of unearning cash assets which they are now required to hold as reserves. The proposal is to count vault cash as part of the required reserves and to reduce the reserve requirements from the present levels (20 per cent for central reserve city banks in New York and Chicago, i8 per cent for reserve city banks in some 50 of the largest cities, and I2 per cent for smaller banks) to a uniform io per cent.' Of the $9.8 billion, $7.7 billion is accounted for by the reduction in reserve requirements and $2.I billion is accounted for by the inclusion of vault cash as part of required reserves. It is evident that only a very small part of the windfall would accrue to the smaller socalled country banks which hold about 38 per cent of the total assets of member banks. The proposal, if enacted into law, would conspicuously favor the large banks. American history is replete with government subsidies on a handsome scale. In many, possibly even in most cases, these subsidies from the railroad land grants to low-cost housing -can be justified from the standpoint of the general welfare. But no one will deny, I think, that there are few if any actions of government that demand a more conscientious assessment of general social benefits and costs. Subsidies, open or veiled, should continually be subjected to careful scrutiny. And this is especially true of subsidies which are veiled in mystery as is the case with the one here under consideration. The Commission says that a clear-cut understanding on the part of the public is highly important. Unfortunately, the report falls considerably short of this worthy aim. Still there is no need to feel alarmed. The Congress has evidenced in recent years a high degree of enlightenment with respect to monetary and banking matters and is not likely to act hastily on this proposal. World War II could have been financed entirely (apart from taxes and bond sales to the public) by the Federal Reserve Banks. This would have involved no subsidy to anybody. The war was indeed partly financed in this manner. The Federal Reserve Banks absorbed about $22 billion of new United States securities. The commercial banks, however, absorbed much more, about $69 billion. To enable them to acquire this huge volume of earning assets, they were supplied with the requisite reserves. This cost the banks not a cent. Some economists objected strongly to this procedure. They wanted the Federal Reserve to do all the bank financing in order to prevent the bestowal of a huge windfall of earning assets on the commercial banks. The policy pursued could, however, be justified. The volume of monetary transactions was rising by leaps and bounds under the rapidly growing war economy. This development involved huge increases in the cost of banking operations. War financing involved extensive banking services performed for the Treasury by the banks. Had the war bankfinancing been done exclusively by the Federal Reserve, the commercial banks would have had to be subsidized in some other manner, or else they would have been compelled to charge unbearably high service charges. The Economic Policy Commission deplores the fact that the Federal Reserve Banks had absorbed so high a proportion of the war issues. The commercial banks could have done the job with less use of Federal Reserve credit had the reserve requirements been reduced. Had this been done, nearly all of the asset windfalls would have fallen to the commercial banks and virtually none to the Federal Reserve Banks. The Commission now wishes to back The report suggests that this may be lowered or raised by the Federal Reserve Board within the range of 8 and I2 per cent.